DSM Systems for Multi-Processor Architectures Using AI-Driven Test Case Generation - Arya, Devendra (Journal for Research in Applied Sciences and Biotechnology, 2022)
This research paper explores the critical domain of automated. It also examines automated test execution frameworks, real-time monitoring solutions, and advanced verification and validation techniques. The findings of this study contribute to the advancement of DSM testing methodologies and provide valuable insights for both researchers and practitioners in the field of distributed systems and parallel computing. The research highlights the challenges faced in DSM testing, such as scalability issues and non-determinism, and proposes future directions for research, including the integration of artificial intelligence and cloud-based testing platforms.